From Donor to Ndoro: Donor Neocolonialism, Worker Vulnerability, and Solidarity for the Sustainability of the Indonesian Women's Movement - Nathania Theora Warokka; Graciella Annette Warokka; Nabila Isnandini (Universitas Muhammadiyah Ponorogo, 2026)
A donor relationship with civil society organizations (CSOs) is a relationship that is characterized by dependence caused by unequal power relations. This research aims to explore the importance of solidarity in the context of the sustainability of the Indonesian women's movement in the midst of this problem. Unlike previous studies, this study used the practice of vigilant eco-love in analyzing solidarity within the women's movement. In its approach, this study used a reflective thematic analysis method that emphasized themes in qualitative data obtained through semi-structured in-depth interviews. Interview participants were four figures who were significantly involved in the women's movement in Indonesia. This study identifies three themes: 1) donor neo-colonialism within CSO in Indonesia, 2) the vulnerability of CSO workers in sustainability issues, and 3) the importance of vigilant eco-love for sustainable women's movements. The study argues that the vigilant eco-love practice is the key to answering questions regarding the sustainability of the women's movement and the vulnerability of workers amidst the attack of donor neoliberal colonization. Nonetheless, the study has key limitation in the form of limited number of participants. Future studies might benefit from widening the pool of participant to donors and intermeary donors, as well as exploring the aspect of power relations between CSOs and their resources. Keywords: Donor Neo-Colonialism; Worker Vulnerability; Women's Movement; Sustainability; Vigilant Eco-Love;